2019
DOI: 10.1177/2333393619852935
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Change and Nonsuicidal Self-Injury: A Qualitative Interview Study With Individuals at Various Stages of Change

Abstract: Nonsuicidal self-injury (NSSI) is a pervasive and potentially lethal behavior that affects many youth and adolescents. Effective treatment and prevention efforts are critical but often lack a nuanced understanding of the behavior change process. To address this gap, this research employs a stage of change model to identify and understand the most salient and widespread processes that facilitate NSSI behavior change. Thirty-one semi-structured interviews were conducted with individuals with current or past self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 68 publications
3
69
0
1
Order By: Relevance
“…A key theme across these efforts is that people with lived experience do not conceptualize recovery as just behavioral cessation. They report ongoing thoughts and urges and an ambivalence about completely stopping a behavior that has proven an effective coping strategy (Grunberg & Lewis, 2015; Kruzan & Whitlock, 2019). They also talk about the ongoing effects of self‐injury (e.g., scarring; Lewis & Mehrabkhani, 2016), the perpetual stigma associated with NSSI, and how they navigate ongoing disclosures (Lewis et al, 2019; Long, 2018).…”
Section: Research On Nssi Recoverymentioning
confidence: 99%
“…A key theme across these efforts is that people with lived experience do not conceptualize recovery as just behavioral cessation. They report ongoing thoughts and urges and an ambivalence about completely stopping a behavior that has proven an effective coping strategy (Grunberg & Lewis, 2015; Kruzan & Whitlock, 2019). They also talk about the ongoing effects of self‐injury (e.g., scarring; Lewis & Mehrabkhani, 2016), the perpetual stigma associated with NSSI, and how they navigate ongoing disclosures (Lewis et al, 2019; Long, 2018).…”
Section: Research On Nssi Recoverymentioning
confidence: 99%
“…Research [eg., (17)] has shown that stigma related to NSSI as well as negative reactions (online/offline) increases the risk for NSSI and may create help-seeking barriers, and should, therefore, be targeted in the prevention of NSSI. Unfortunately, while there has been an increase in our understanding over the past decade of the factors that govern risk of NSSI [e.g., (18)], the development of evidence-based approaches for prevention remained nascent (18). In their review of NSSI prevention literature, primarily based on lessons learned from related health challenges, Heath et al (19) and Kruzan & Whitlock (18) layout key considerations for evidence-based prevention programs targeting NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…(19)]. Some NSSI scholars who have considered this issue [e.g., (18,28)] argue that effective school-based prevention will need to include NSSI-specific psychoeducation aimed at increasing awareness of NSSI as well as clear strategies for stopping the spread of contagion (and other NSSI-related factors such as NSSI stigma) in order to be effective to prevent/delay onset. However, most schools are afraid for potential iatrogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Given that even a single incident of NSSI remains a harmful dysregulated behavior that has a long-lasting and detrimental effect on an adolescent’s well-being [ 6 ], numerous studies have been dedicated to finding the risk factors of NSSI initiation among adolescents [ 7 , 8 , 9 , 10 ]. Moreover, the majority of adolescents who conduct NSSI finally remit the behavior [ 11 ].…”
Section: Introductionmentioning
confidence: 99%